CD10 expression identifies a subset of human perivascular progenitor cells with high proliferation and calcification potentials. (19th November 2019) - Ding, Lijun; Vezzani, Bianca; Khan, Nusrat; Su, Jing; Xu, Lu; Yan, Guijun; Liu, Yong; Li, Ruotian; Gaur, Anushri; Diao, Zhenyu; Hu, Yali; Yang, Zhongzhou; et al.
Abstract: The tunica adventitia ensheathes arteries and veins and contains presumptive mesenchymal stem cells (MSCs) involved in vascular remodeling. We show here that a subset of human adventitial cells express the CD10/CALLA cell surface metalloprotease. Both CD10 + and CD10 − adventitial cells displayed phenotypic features of MSCs when expanded in culture. However, CD10 + adventitial cells exhibited higher proliferation, clonogenic and osteogenic potentials in comparison to their CD10 − counterparts. CD10 + adventitial cells increased expression of the cell cycle protein CCND2 via ERK1/2 signaling and osteoblastogenic gene expression via NF-κB signaling. CD10 expression was upregulated in adventitial cells through sonic hedgehog-mediated GLI1 signaling. These results suggest that CD10, which marks rapidly dividing cells in other normal and malignant cell lineages, plays a role in perivascular MSC function and cell fate specification. These findings also point to a role for CD10 + perivascular cells in vascular remodeling and calcification. : Abstract : Sonic hedgehog (SHH)/GLI1/CD10 signaling in the perivascular niche (Figure S8). SHH secreted in the perivascular niche induces GLI1 and CD10 expression. CD10 can upregulate CCND2 expression via ERK1/2 and stimulate NELL1 expression via NF-κB, which leads to self-renewal and high osteogenic potential in human adventitial cells.